2013
DOI: 10.1210/me.2013-1159
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of iNOS Gene Transcription by IL-1β and IFN-γ Requires a Coactivator Exchange Mechanism

Abstract: The proinflammatory cytokines IL-1β and IFN-γ decrease functional islet β-cell mass in part through the increased expression of specific genes, such as inducible nitric oxide synthase (iNOS). Dysregulated iNOS protein accumulation leads to overproduction of nitric oxide, which induces DNA damage, impairs β-cell function, and ultimately diminishes cellular viability. However, the transcriptional mechanisms underlying cytokine-mediated expression of the iNOS gene are not completely understood. Herein, we demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
36
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 79 publications
2
36
1
1
Order By: Relevance
“…Current literature mainly focuses on how IFN-g potentiates LPS-induced gene expression. For several typical M1 marker genes, it was very elegantly shown how STAT1, the transcription factor activated by IFN-g, helps NF-kB to increase inflammatory gene transcription (9,27,28). Although in our study we also found LPS-induced genes, including typical M1 markers like Nos2 and Il12b, to be upregulated, we identified an even larger proportion of LPS-induced genes that were repressed by prior IFN-g priming.…”
Section: Discussioncontrasting
confidence: 44%
“…Current literature mainly focuses on how IFN-g potentiates LPS-induced gene expression. For several typical M1 marker genes, it was very elegantly shown how STAT1, the transcription factor activated by IFN-g, helps NF-kB to increase inflammatory gene transcription (9,27,28). Although in our study we also found LPS-induced genes, including typical M1 markers like Nos2 and Il12b, to be upregulated, we identified an even larger proportion of LPS-induced genes that were repressed by prior IFN-g priming.…”
Section: Discussioncontrasting
confidence: 44%
“…Accordingly, interfering with STAT1 abundance or activity diminishes production of the chemoattractant signals that promote immune cell invasion into islets. In addition, diminishing STAT1 activity also impacts the IL-1␤-mediated expression of the inducible nitric oxide synthase (iNOS) gene (8). The expression of iNOS and subsequent production of NO is strongly associated with losses in functional ␤-cell mass (15)(16)(17)70).…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory cytokines such as IL-1␤ and IFN␥ contribute significantly to losses in islet ␤-cell viability and insulin secretion. Islet ␤-cells exposed to IL-1␤ and IFN␥ undergo extensive genetic reprogramming, which includes transcriptional increases in the inducible nitric oxide synthase (iNOS) gene (13,26) and various genes encoding chemokines (8 -10, 12, 44).…”
mentioning
confidence: 99%
“…IL-1␤ induces the expression of the iNOS gene, promoting marked accumulation of iNOS protein, a phenotype potentiated by the addition of IFN␥ (13,16,17,26). The active iNOS enzyme produces nitric oxide, a free radical signaling molecule that impacts numerous cellular functions (5,28,46).…”
mentioning
confidence: 99%
See 1 more Smart Citation